Bisphosphonate-induced atypical subtrochanteric femoral fracture - Vaishya, Raju (BMJ Publishing Group, 2013)
The use of bisphosphonates (BPs) is universally accepted in the management of osteoporosis. However, a small percentage of patients have been recognised to develop atypical subtrochanteric fractures of the femur with the prolonged use of BPs. We report a rare case of bilateral insufficiency lesions in the proximal femora, where a major subtrochanteric fracture developed with a minor fall. This was successfully treated with internal fixation using proximal femoral nail.